Coastal Women in International Climate Media: Ecolinguistic Framing Analysis - Dian Rahmawati Arief; Zulfiqri Saputra Samsul (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examines how international climate media constructs coastal women through grammatical choice and ecolinguistic framing. Drawing on Halliday's transitivity system and Stibbe's ecolinguistic framework, the study analyses 20 finite clauses extracted from 30 international news articles published between 2021 and 2025. The analysis asks what process types and participant roles are assigned to coastal women, what frames are produced through those choices, and what ecological meanings are foregrounded or erased. The findings show that material processes dominate the corpus: 18 of the 20 clauses contain a material component, and women appear in Actor roles in 14 clauses when dual-role structures are included. This pattern constructs coastal women mainly as workers, leaders, conservation actors, and climate-resilience agents rather than as passive victims. However, the analysis also identifies displaced agency in clauses where climate forces, institutions, or unnamed development actors occupy the active grammatical position, while women appear as affected participants, clients, or beneficiaries. Ecolinguistically, the corpus is therefore beneficial in recognising women's practical and political agency, but ambivalent in its recurring erasure of structural causes such as unequal coastal governance, exclusion from fisheries policy, and insecure land or livelihood rights. The study contributes to ecolinguistic media analysis by showing that grammatical agency alone is not enough; climate journalism must also name the power relations that make coastal women's resilience necessary.